Aqueous-Phase Partial Oxidation of Methane over Pd−Fe/ZSM-5 with O2 in the Presence of H2 - Yang, Gun Sik; Kang, Jongkyu; Park, Eun Duck (ChemCatChem, 2023)
The selective oxidation of methane into methane oxygenates such as CH3OH and HCOOH with O2 is a promising technology for direct methane conversion. This study successfully demonstrates the partial oxidation of methane over Pd−Fe/ZSM-5 catalysts in water, where H2O2 was generated in situ from H2 and O2. A low Pd content is essential for preventing agglomeration of Pd nanoparticles, and intimate contact between Pd and Fe species is beneficial for achieving high yields of methane oxygenates. This one-body catalyst showed better catalytic performance than that of previously reported ones, especially at low temperatures. 0.28 %Pd–0.56 %Fe/ZSM-5 exhibited a stable catalytic performance in a continuous flow reactor.
Keywords: Aqueous phasis; Catalytic performance; Fe-ZSM-5 catalysts; Fe/ZSM-5; Fe/ZSM-5 catalyst; Methane conversions; Partial oxidations of methane; Pd−fe/ZSM-5; Selective oxidation; hydrogen peroxide; methanol; partial oxidation of methane; Pd−Fe/ZSM-5; stability